Genome-Wide Identification and Characterization of bHLH Transcription Factors Related to Anthocyanin Biosynthesis in Red Walnut (Juglans regia L.) - Zhao, Wei; Liu, Yonghui; Li, Lin; Meng, Haijun; Yang, Ying; Dong, Zhaobin; Wang, Lei; Wu, Guoliang (Frontiers in Genetics, 2021)
Basic helix-loop-helix (bHLH) proteins are transcription factors (TFs) that have been shown to regulate anthocyanin biosynthesis in many plant species. However, the bHLH gene family in walnut (Juglans regia L.) has not yet been reported. In this study, 102 bHLH genes were identified in the walnut genome and were classified into 15 subfamilies according to sequence similarity and phylogenetic relationships. The gene structure, conserved domains, and chromosome location of the genes were analyzed by bioinformatic methods. Gene duplication analyses revealed that 42 JrbHLHs were involved in the expansion of the walnut bHLH gene family. We also characterized cis-regulatory elements of these genes and performed Gene Ontology enrichment analysis of gene functions, and examined protein–protein interactions. Four candidate genes (JrEGL1a, JrEGL1b, JrbHLHA1, and JrbHLHA2) were found to have high homology to genes encoding bHLH TFs involved in anthocyanin biosynthesis in other plants. RNA sequencing revealed tissue- and developmental stage-specific expression profiles and distinct expression patterns of JrbHLHs according to phenotype (red vs green leaves) and developmental stage in red walnut hybrid progeny, which were confirmed by quantitative real-time PCR analysis. All 4 of the candidate JrbHLH proteins localized to the nucleus, consistent with a TF function. These results provide a basis for functional characterization of bHLH genes and investigations on the molecular mechanisms of anthocyanin biosynthesis in red walnut.